Kinerja Keuangan Sebelum dan Masa Pandemi Covid-19 Pada Perusahaan BUMN - Amir Hasan; Nasharuddin Mas; Ana Sopanah (Politeknik Ganesha Medan, 2022)
This study aims to determine the impact of the Covid-19 pandemic on the company's financial performance. In this study, the approach used by researchers was quantitative and comparative research. The population of this study is all construction service companies of State-Owned Enterprises listed on the Indonesia Stock Exchange in the period before the Covid-19 pandemic (2018-2019) and during the Covid-19 pandemic (2020-2021), totaling 4 companies. The data source used in this study is secondary data, from annual reports. In this study, the analytical methods used are descriptive quantitative analysis and inferential analysis. Inferential statistical analysis used in this study were paired sample t-test and independent sample t-test. The results of the overall hypothesis test show that there are differences in financial performance between before and during the Covid-19 pandemic, state-owned construction service companies listed on the Indonesia Stock Exchange. Over the past four years, infrastructure development carried out by state-owned construction companies has experienced a good increase. Problems occurred when the spread of the Covid-19 virus began in 2019 which resulted in 2020 infrastructure development being delayed. The delay in the end also affected the financial condition of SOEs. For companies, profits are not only ways and efforts to increase them, but also think about what to do to improve company performance so that they can maintain stability, growth and achievement on profits. The company's performance is related to the company's efforts in managing the resources it has in generating profits that can increase the company's prosperity.